ANALISIS PENGARUH CAR, NPL, NIM, DAN LDR TERHADAP ROA PADA BANK UMUM SWASTA NASIONAL DI INDONESIA - WIBISONO, KUNTO (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRAC This research is performed on order to test the influence of the variable Capital Adequacy Ratio (CAR), Non Performing Loan (NPL, Net Interest Margin (NIM) and Loan to Deposit Ratio (LDR) toward Return on asset (ROA). Methodology research as the sample used purposive sampling, sample was accured 20 Bank Swasta Nasional In Indonesia. Data analysis with multi liniear regression of ordinary least square and hypotheses test used t-statistic and F-Statistic at level of significance 5%, a classic assumption examination which consist of data normality test, multicoliniearity test, heteroskedasticity test and autocorrelation test is also being done to test the hypotheses. During research period show as variabel and data research was normal distributed . Based on test , multicolinearity test, heterosskedasticity test and autocorrelation test classic assumption deviation has no founded, this indicate that the available data has fulfill the condition to use multi linear regression model. This Result of research show that variabel NPL and LDR negative did not significant influence toward ROA. Variable CAR and NIM positive significant influence significant toward ROA. Prediction capability from these four variable toward ROA is 47% where the balance 53 % is affected to other factor which was not to be entered to be research model. Key Words : Return On asset (ROA), Capital Adequacy Ratio (CAR), Non Performing Loan ( NPL), Net Interest Margin (NIM), and Loan to Deposit Ratio (LDR).